Global analysis of phosphoproteome dynamics in embryonic development of zebrafish (Danio rerio). Issue 1 (7th December 2015) - Kwon, Oh Kwang; Kim, Sun Ju; Lee, You‐Mie; Lee, Young‐Hoon; Bae, Young‐Seuk; Kim, Jin Young; Peng, Xiaojun; Cheng, Zhongyi; Zhao, Yingming; Lee, Sangkyu
Abstract : The zebrafish ( Danio rerio ) is a popular animal model used for studies on vertebrate development and organogenesis. Recent research has shown a similarity of approximately 70% between the human and zebrafish genomes and about 84% of human disease‐causing genes have common ancestry with that of the zebrafish genes. Zebrafish embryos have a number of desirable features, including transparency, a large size, and rapid embryogenesis. Protein phosphorylation is a well‐known PTM, which can carry out various biological functions. Recent MS developments have enabled the study of global phosphorylation patterns by using MS‐based proteomics coupled with titanium dioxide phosphopeptide enrichment. In the present study, we identified 3500 nonredundant phosphorylation sites on 2166 phosphoproteins and quantified 1564 phosphoproteins in developing embryos of zebrafish. The distribution of Ser/Thr/Tyr phosphorylation sites in zebrafish embryos was found to be 88.9, 10.2, and 0.9%, respectively. A potential kinase motif was predicted using Motif‐X analysis, for 80% of the identified phosphorylation sites, with the proline‐directed motif appearing most frequently, and 35 phosphorylation sites having the pSF motif. In addition, we created six phosphoprotein clusters based on their dynamic pattern during the development of zebrafish embryos. Here, we report the largest dataset of phosphoproteins in zebrafish embryos and our results can be used for further studies on phosphorylation sites or phosphoprotein dynamics in zebrafish embryos.